Effect of Current on Plasma Parameters Resulting from the Wires-Exploding Technique of Copper Material - ojs_admin, (University of Thi-Qar Journal of Science, 2020)
In this research the diagnostic of optical emission spectroscopy from exploding copper wires have done for different current. By using Boltzman plot can be calculated the plasma electron temperature , and by using Stark broadening can be evaluated the electron density for different current of (75, 100 and 150)A with diameter 0.25 mm in deionized water. It was observed that the electron density decrease with an increasing the current from 75 A to 150 A while the electron temperatures increase for the same current. The plasma has a peak 652 nm corresponding to Hα line for .hydrogen .atoms which obtained from .optical emission spectrum (OES), the peaks belong to atomic copper lines. The plasma electron temperature related with emission line intensity and number .density with the formed copper nanoparticles size was studied.